Respuesta :
[tex] \qquad \qquad \bf \huge\star \: \: \large{ \underline{Answer} } \huge \: \: \star[/tex]
[tex]\qquad❖ \: \sf \:x = - \dfrac{ 9}{20} [/tex]
[tex]\textsf{ \underline{\underline{Steps to solve the problem} }:}[/tex]
[tex]\qquad❖ \: \sf \:2(3x + 1) + 3(5x + 2) = x - 1[/tex]
[tex]\qquad❖ \: \sf \:6x + 2 + 15x + 6 = x - 1[/tex]
[tex]\qquad❖ \: \sf \:(6x + 15x - x) + (2 + 6 + 1) = 0[/tex]
[tex]\qquad❖ \: \sf \:20x + 9 = 0[/tex]
[tex]\qquad❖ \: \sf \:20x = - 9[/tex]
[tex] \qquad \large \sf {Conclusion} : [/tex]
[tex]\qquad❖ \: \sf \:x =- \cfrac{ 9}{20} [/tex]
[tex]\huge\underline{\red{A}\green{n}\blue{s}\purple{w}\pink{e}\orange{r} →}[/tex]
x = –9/20
Step-by-step explanation:
________________________________
→ 2(3x + 1) + 3(5x + 2) = x – 1
→ 6x + 2 + 15x + 6 = x – 1
→ 21x + 8 = x – 1
→ 21x – x = – 1 – 8
→ 20x = – 9
→ x = –9/20
________________________________